To Problem on Power Saving at Asphalt-Concrete Plants - B. M. Khroustalev; Y. N. Kovalev; A. P. Nesenchuk; V. N. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a complex of measures directed on gross maximum realization of power saving potential while producing asphalt-concrete mixture.